Glutathione Modulates Hydrogen Sulfide Release and the Ocular Hypotensive Action of Diallyl Polysulfide Compounds - Susmit Mhatre; Rai Anjali; Pulkit Sahai; John Auden; Somnath Singh; Ya Fatou Njie Mbye; Sunny E. Ohia; Catherine A. Opere (MDPI AG, 2024)
Background: Hydrogen sulfide (H2S) is an endogenous transmitter with the potential to regulate aqueous humor dynamics and protect retinal neurons from degeneration. The aim of the present study was two-fold: (a) to evaluate the release of H2S from two polysulfides, diallyl disulfide (DADS), and diallyl trisulfide (DATS); and (b) to investigate their ocular hypotensive actions in normotensive male and female rabbits in the presence and absence of GSH. Materials and Methods: H2S was quantified hourly for up to 6 h using a H2S-Biosensor (World Precision Instruments, Sarasota, Fl). Intraocular pressure (IOP) was assessed in normotensive New Zealand Albino rabbits using a pneumotonometer (model 30 classic; Reichert Ophthalmic Instruments, Depew, NY, USA). Results: In the presence of GSH, there was an increase in the in vitro release of H2S produced by DADS and DATS. Both DADS and DATS also caused a dose-dependent reduction in IOP in male and female rabbits, in both treated and untreated eyes. For instance, in male animals, the presence of GSH (3% and 5%) significantly (p < 0.05, n = 5) enhanced the ocular hypotensive action of DADS (2%) and DATS (2%) from 14.02 ± 2.89% to 18.67 ± 5.6% and from 16.22 ± 3.48 to 23.62 ± 5.79%, respectively. Conclusions: GSH enhanced both H2S release and ocular hypotensive action of the polysulfides in a manner that was dependent on the number of sulfur atoms present in each polysulfide. Furthermore, female animals were less sensitive to the IOP-lowering action of the polysulfides, when compared to their male counterparts.